Peran Kyai dalam Pengelolaan Pesantren di Era Global - Jauharotun Nafisatul Ulya; Anisah Triyuliasari (Jurnal Pendidikan Nusantara, 2024)
Education is necessary to face life in the future. In this modern era, the selection of educational institutions is necessary, so that the education institutions based on the curriculum of the trainees are in great demand. The development of the peasantry is progressing and is now widely known by society for its success in giving birth to a better generation for our nation. The organized and planned training programmes have been respected by both the public and formal institutions. The aim of this research is to investigate and evaluate the role of kyai in training management during the current era's rapid evolution. In today's era, there are many challenges faced by teachers in the management of the classroom, therefore, the teacher or the ustadz must be able to cope with the challenges in the administration of the schoolroom. The research uses methods of qualitative approach and data collection by means of observations and interviews at the Modern Cottage Arrisalah Ponorogo. As a result of this research, it is known that Kyai's role is very influential in educating her mother-in-law. Not only to act as a Kyai, but also to innovate and make changes in the management of the competition to continue to flourish in the era of technology that continues to modernize.